Diagnosis and status of the communication units in companies of Lambayeque, Perú: from the DIRCOM’S vision - Alarcón Llontop, Luis Rolando (2017)
In Peru, the number of companies is increasing. While around the world the director of communication, DirCom, takes hold, in Peru its incorporation is slow. Without previous studies on the subject of DirCom in Lambayeque, this research  based on positivist paradigm, quantitative approach, and descriptive level, was applied on a convenience sample of companies using two surveys as techniques and their questionnaires as instruments. The result of the diagnosis shows that although companies declare to comply with organizational and institutional indicators, their credit declines when it is objectified in their own communicational indicators, such as the image audit and the integral communication plan. Regarding the status of the communication units, there are certain incongruities such as the dependence of the communication manager, their degree or that the definition of the communication strategy is not defined by the communication director.